Quo Vadis Radiotherapy? Technological Advances and the Rising Problems in Cancer Management - Allen, Barry J. (Hindawi Publishing Corporation, 2013)
Purpose. Despite the latest technological advances in radiotherapy, cancer control is still challenging for several tumour sites. The survival rates for the most deadly cancers, such as ovarian and pancreatic, have not changed over the last decades. The solution to the problem lies in the change of focus: from local treatment to systemic therapy. The aim of this paper is to present the current status as well as the gaps in radiotherapy and, at the same time, to look into potential solutions to improve cancer control and survival. Methods. The currently available advanced radiotherapy treatment techniques have been analysed and their cost-effectiveness discussed. The problem of systemic disease management was specifically targeted. Results. Clinical studies show limited benefit in cancer control from hadron therapy. However, targeted therapies together with molecular imaging could improve treatment outcome for several tumour sites while controlling the systemic disease. Conclusion. The advances in photon therapy continue to be competitive with the much more expensive hadron therapy. To justify the cost effectiveness of proton/heavy ion therapy, there is a need for phase III randomised clinical trials. Furthermore, the success of systemic disease management lies in the fusion between radiation oncology technology and microbiology.